Cardiac myosin activators for heart failure therapy: focus on omecamtiv mecarbil - Edgardo Kaplinsky; Gordon Mallarkey (BioExcel Publishing Ltd, 2018)
Heart failure continues to be a major global health problem with a pronounced impact on morbidity and mortality and very limited drug treatment options especially with regard to inotropic therapy. Omecamtiv mecarbil is a first-in-class cardiac myosin activator, which increases the proportion of myosin heads that are tightly bound to actin and creates a force-producing state that is not associated with cytosolic calcium accumulation. Phase I and phase II studies have shown that it is safe and well tolerated. It produces dose-dependent increases in systolic ejection time (SET), stroke volume (SV), left ventricular ejection fraction (LVEF), and fractional shortening. In the ATOMIC-AHF trial, intravenous (IV) omecamtiv mecarbil did not improve dyspnoea overall but may have improved it in a high-dose group of acute heart failure patients. It did, however, increase SET, decrease left ventricular end-systolic diameter, and was well tolerated. The COSMIC-HF trial showed that a pharmacokinetic-based dose-titration strategy of oral omecamtiv mecarbil improved cardiac function and reduced ventricular diameters compared to placebo and had a similar safety profile. It also significantly reduced plasma N-terminalpro B-type natriuretic peptide compared with placebo. The GALACTIC-HF trial is now underway and will compare omecamtiv mecarbil with placebo when added to current heart failure standard treatment in patients with chronic heart failure and reduced LVEF. It is expected to be completed in January 2021. The ongoing range of preclinical and clinical research on omecamtiv mecarbil will further elucidate its full range of pharmacological effects and its clinical usefulness in heart failure.